2012
DOI: 10.1128/jvi.01549-12
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Chromatin Immunoprecipitation with Promoter Sequence Microarray Analysis of the Interaction of the NSs Protein of Rift Valley Fever Virus with Regulatory DNA Regions of the Host Genome

Abstract: dRift Valley fever virus (RVFV) is a highly pathogenic Phlebovirus that infects humans and ruminants. Initially confined to Africa, RVFV has spread outside Africa and presently represents a high risk to other geographic regions. It is responsible for high fatality rates in sheep and cattle. In humans, RVFV can induce hepatitis, encephalitis, retinitis, or fatal hemorrhagic fever. The nonstructural NSs protein that is the major virulence factor is found in the nuclei of infected cells where it associates with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 45 publications
1
28
1
1
Order By: Relevance
“…In any case, the removal of FBXO3 from the nucleus may have implications for NSs regulation, liberating NSs to pursue another activity such as, e.g., PKR degradation. Interestingly, a recent chromatin immunoprecipitation-DNA sequencing (CHIP-Seq) study revealed that RVFV NSs also downregulates the promoter of the FBXO3 gene (43). Although in our experiments mRNA levels of FBXO3 were unaffected by NSs at 6 h postinfection (p.i.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…In any case, the removal of FBXO3 from the nucleus may have implications for NSs regulation, liberating NSs to pursue another activity such as, e.g., PKR degradation. Interestingly, a recent chromatin immunoprecipitation-DNA sequencing (CHIP-Seq) study revealed that RVFV NSs also downregulates the promoter of the FBXO3 gene (43). Although in our experiments mRNA levels of FBXO3 were unaffected by NSs at 6 h postinfection (p.i.…”
Section: Discussioncontrasting
confidence: 44%
“…In addition to the effects on IFN induction, host transcription, inflammatory cytokine production, p53 regulation, and PKR degradation, RVFV NSs induces chromosomal anomalies (44) and regulates many other genes involved in innate immunity, inflammation, cell adhesion, axonal guidance, development, and blood coagulation (43). Thus, NSs of RVFV is a multifunctional protein that dysregulates and damages the host at several levels.…”
Section: Discussionmentioning
confidence: 99%
“…NSs does not only interact with promoters of the innate-immunity regulating genes such as IFN-β, and those involved in inflammation, IL10Rb, but also with the promoters of a number of genes involved in coagulation, cell adhesion and neurological functions. The effect on the expression of these genes can help us to further understand the pathological effects seen upon RVFV infection [59]. …”
Section: Genus Phlebovirusmentioning
confidence: 99%
“…While fos is widely studied in multiple diseases as well as its role in apoptosis, the nuclear receptor family of intracellular transcription factors is understudied, especially in the context of acute infection. Furthermore, a previous study identified NSs as interacting with the nr4a2 promoter through chromatin immunoprecipitation coupled with DNA microarray (ChIP-chip) analysis, prompting further examination of this particular gene (Benferhat et al, 2012). To determine if the observed STAT3 effects are due to a direct interaction of STAT3 with the nr4a2 promoter, ChIP was performed.…”
Section: Resultsmentioning
confidence: 99%
“…NSs has previously been detected at the IFN-β promoter (Le May et al, 2008) and bound to pericentromeric DNA (Mansuroglu et al, 2010). The interaction of NSs with promoters was also studied on a global scale using the ChIP-on-chip technique (Benferhat et al, 2012). Supplemental data from this publication indicated that NSs was present at the promoter of nr4a2 and fosl2 , a fos family member.…”
Section: Discussionmentioning
confidence: 99%